Mexican philosophy for the 21st Century Relajo, Zozobra, and other frameworks for understanding Our World - Sánchez, Carlos Alberto 1975- (London Bloomsbury Academic, 2023)
"A sustained reflection on distinctly Mexican concepts that reveals the value of applying Mexican thought to everyday life"-- Provided by publisher.
Introduction: Mexican Philosophy: What Is It and Why It Matters -- Relajo -- Nepantla -- Zozobra -- Corazonada -- Tik -- Figure of the World -- Mexistentialism.
Includes bibliographical references (pages 205-212) and index.
Keywords: Philosophy, Mexican